2017
DOI: 10.1007/s12640-017-9743-8
|View full text |Cite
|
Sign up to set email alerts
|

β-N-Methylamino-L-Alanine Toxicity in PC12: Excitotoxicity vs. Misincorporation

Abstract: The implication of β-N-methylamino-L-alanine (BMAA) in the development of neurodegenerative diseases worldwide has led to several investigations of the mechanism, or mechanisms, of toxicity of this cyanobacterially produced amino acid. The primary mechanism of toxicity that was identified is excitotoxicity, with a second possible mechanism, the misincorporation of BMAA into the primary protein structure and consequent cell damage, having been more recently reported. However, studies on excitotoxicity and misin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Although Dunlop et al [ 16 ] reported the misincorporation of BMAA in a human lung fibroblast cell line and in human umbilical vein endothelial cells, by virtue of detection of BMAA in the protein fraction, no toxicity in these cell lines was reported whereas toxicity was reported for the neuroblastoma cell line used in the same study, suggesting excitotoxicity as a mechanism. Van Onselen et al [ 69 ] showed that differentiation of a rat pheochromocytoma cell line (PC12) with nerve growth factor, with resulting expression of glutamate receptors, was required in order to achieve BMAA toxicity, presumably via an excitotoxic mechanism. Differentiation of the same cell line was not required to observe toxicity in response to l -canavanine exposure, indicating different mechanisms of toxicity of these two compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Dunlop et al [ 16 ] reported the misincorporation of BMAA in a human lung fibroblast cell line and in human umbilical vein endothelial cells, by virtue of detection of BMAA in the protein fraction, no toxicity in these cell lines was reported whereas toxicity was reported for the neuroblastoma cell line used in the same study, suggesting excitotoxicity as a mechanism. Van Onselen et al [ 69 ] showed that differentiation of a rat pheochromocytoma cell line (PC12) with nerve growth factor, with resulting expression of glutamate receptors, was required in order to achieve BMAA toxicity, presumably via an excitotoxic mechanism. Differentiation of the same cell line was not required to observe toxicity in response to l -canavanine exposure, indicating different mechanisms of toxicity of these two compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for non-primary protein association in favor of misincorporation also exists [ 34 ]. Furthermore, despite reports that BMAA does not misincorporate into proteins in bacteria or in a rat pheochromocytoma cell line [ 34 , 69 ] it has been suggested that the lack of prokaryote misincorporation may not hold true in eukaryotes [ 75 ], although the authors cite Glover et al [ 32 ] in support of their hypothesis, despite their use of a prokaryotic expression system. In this study, human cell lines were therefore used to evaluate BMAA misincorporation using both toxicological markers and amino acid compositional analysis of purified proteins from exposed cell lines, with reference to known misincorporating amino acid analogues.…”
Section: Introductionmentioning
confidence: 99%
“…It is also suggested that BMAA incorporates neuronal proteins, and substitutes for ala or ser residues, potentially inducing protein misfolding, aggregation mechanisms and cellular apoptosis [ 45 ]. But this hypothesis is controversial and recent in vitro data propose that BMAA does not misincorporate into proteins, adding to the complexity of its precise mode of action [ 92 ]. However, if confirmed, the incorporation of the toxin in proteins might explain its toxic bioaccumulation in cells coupled with a progressive release of BMAA in the CNS over the years, as a function of the protein turnover.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relevant research, at least in the case of BMAA shows that wholesale misincorporation of non-protoeinogenic amino acids is not easily achieved in living cells [253], [254]. BMAA misincorporation is resisted even in bacteria [242], though misincorporation can be humanly engineered and achieved efficiently in vitro under special conditions [251], [255], [256].…”
Section: Approaching and Penetrating The Nuclear Envelopementioning
confidence: 99%